Therapeutic Effect of Electronic Endoscopic Hematoma Removal on Hypertensive Basal Ganglia Cerebral Hemorrhage Based on Smart Medical Technology. (9th June 2021) - Wu, Yiping; Zhang, Shan; Dong, Yu; Shen, Xiangzhu; Han, Yafei; Li, Yimeng; Xu, Wei; Ma, Ke; Tang, Huichang; Yang, Dezhen; Li, Haichang
Abstract : The medical and health industry has successively experienced three stages of digital medical treatment, local area network medical treatment, and internet medical treatment. With the rapid development of technologies such as the Internet of Things, big data, and artificial intelligence, emerging applications and service models have gradually penetrated into all aspects of the medical and health field. At this point, the informatization development process of the medical industry has entered the stage of smart medical treatment. (Smart medical system is a new medical system that improves users' medical experience and provides users with better services. Due to the cumbersome, complicated, and mechanically rigid environment of the past medical service, there was no uniform standard. In order to create a reliable and open medical service environment, an intelligent medical system came into being.). A diversified technical foundation and smart medical protection, conducive to providing patients with high-quality medical services, are established. This article mainly introduces the analysis of the therapeutic effect of smart medical electronic endoscopic hematoma removal on hypertensive basal ganglia cerebral hemorrhage and aims to inject advanced technology and vitality of smart medical treatment into the treatment of hypertensive basal ganglia cerebral hemorrhage by hematoma removal and help the doctor to treat the patient. This article proposes the research methods of smart medical application in the treatment of hypertensive basal ganglia cerebral hemorrhage with electronic endoscopic hematoma removal, including smart medical overview, intracranial hematoma removal for hypertensive basal ganglia cerebral hemorrhage, and smart medical bioelectric signal classification. The recognition algorithm is used to realize the smart medical application of the electronic endoscopic hematoma removal in the treatment of hypertensive cerebral hemorrhage in the basal ganglia area. The experimental results show that the removal of intracranial hematoma based on smart medicine can effectively improve the removal rate of intracranial hematoma, with a recovery rate of 26.73% and a significant efficiency of 36.49%.